Encyclopedia of Polymer Science and Technology 2004
DOI: 10.1002/0471440264.pst497
|View full text |Cite
|
Sign up to set email alerts
|

Ring Opening Polymerization

Abstract: Biodegradable and biocompatible aliphatic polyesters have a great potential as biomaterials and environmentally friendly thermoplastics. An intensive research effort has been devoted to living or at least controlled ring opening polymerization (ROP) of lactones, lactides, and glycolides that contributes enormously to macromolecular engineering of these aliphatic polyesters. The recent progress in the field has been reviewed and discussed in terms of structure/nature of the polymerization promoters. A first sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…ROP has been reviewed in the past in a few articles and book chapters. [8][9][10][11] The present review differs in content and in style from our previous review 11 and also from all other previous reviews on ROP. Moreover, the present review is devoted exclusively to ROP by lithium catalysts/initiators.…”
Section: Introductionmentioning
confidence: 99%
“…ROP has been reviewed in the past in a few articles and book chapters. [8][9][10][11] The present review differs in content and in style from our previous review 11 and also from all other previous reviews on ROP. Moreover, the present review is devoted exclusively to ROP by lithium catalysts/initiators.…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR showed that the multiplet at 4.65 ppm assigned to the CH-Br proton disappeared and that a new multiplet was observed at 3.85 ppm characteristic of the CH-N 3 . 5-azidooxepan-2-one 10 and prop-2-yn-1-yl benzoate 11 were reacted at 35°C in the presence of CuI and Et 3 N. After 2 h, the IR absorption at 2100 cm The lactone 10 is a key derivative for the synthesis of a wide range of new functional lactones because of the variety of the structure of the alkyne that can be involved in the "click" reaction.…”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR spectra were recorded at 400 MHz in the FT mode with a Brucker AN 400 apparatus at 25°C. FT-IR spectra were recorded with a Perkin Elmer One apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Among them, the coordination-insertion polymerization is well studied because it can produce PCL with a clear structure and controllable molecular weights. 6 On the other hand, there are a wide variety of systems used to catalyse the ROP of 3-CL. Currently, the most commonly used catalyst systems mainly contain four types, i.e., metal-based compounds, enzymatic compounds, organic compounds and inorganic acids.…”
Section: Introductionmentioning
confidence: 99%